2023
DOI: 10.36677/elperiplo.v0i44.16266
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del perfil del turista y su relación con la demanda de turismo rural en el Estado de México (México)

Abstract: El turismo rural es una tipología de ocio recreativo que ha cobrado una creciente importancia en los mercados turísticos del centro México, aunque en muchos casos la demanda es incipiente, dada la falta de un producto turístico integral en muchos territorios rurales. El objetivo del artículo es identificar las características del perfil del turista rural, a través del estudio de la demanda en algunos destinos rurales del Estado de México. El análisis fue desarrollado a través de un estudio de caso múltiple, ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, it is observed that tourists who frequent recreational spaces in rural areas tend to be people with a social, educational and professional profile who demonstrate a greater interest in enjoying the countryside as a tourist destination. These tourists usually show a higher level of awareness about the importance of valuing natural and cultural resources through their consumption practices (García Rodea et al, 2023) .…”
Section: Tourist Attractions In Urban and Rural Environmentsmentioning
confidence: 99%
“…However, it is observed that tourists who frequent recreational spaces in rural areas tend to be people with a social, educational and professional profile who demonstrate a greater interest in enjoying the countryside as a tourist destination. These tourists usually show a higher level of awareness about the importance of valuing natural and cultural resources through their consumption practices (García Rodea et al, 2023) .…”
Section: Tourist Attractions In Urban and Rural Environmentsmentioning
confidence: 99%